Anticancer Effect of an Electronically Coupled Oligoferrocene - Zeh, Gina; Haines, Philipp; Miehlich, Matthias; Kienz, Torben; Neidlinger, Andreas; Friedrich, Ralf P.; Alexiou, Christoph; Hampel, Frank; Guldi, Dirk Michael; Meyer, Karsten; Schatz, Jürgen; Heinze, Katja; et al. (Organometallics, 2020)
The mode of anticancer activity of simple ferrocenes often relies on their intracellular oxidation with the formation of cytotoxic ferrocenium species. The former compounds should be considered as prodrugs and derived from them ferroceniums as drugs. The drugs are 17e- organometallic species. Therefore, they are chemically unstable and decompose with formation of free cyclopentadienyl ligands (which are further transformed to more stable species) and iron ions. The short lifetime of ferrocenium drugs limits the anticancer effect of ferrocene prodrugs. In this paper we prepared a series of acylated aminoferrocene monomers, dimers, and higher oligonuclear complexes FcN (where N = 1-4). Drugs [FcN]+ derived from FcN (N > 1) are more stable than monomeric [Fc]+, provided that the ferrocene units are electronically coupled. Correspondingly, we expected that FcN species will be more potent anticancer agents in comparison to the related monomers. These assumptions were confirmed for dimer 10. We observed that this prodrug has sufficient solubility in aqueous solution (100 μM) and favorable lipophilicity (log P = 2.2 ± 0.2). Ferrocene units in 10 are efficiently electronically coupled via a -C(═O)NH- linker according to cyclic voltammetry, differential pulse voltammetry, and spectroelectrochemistry. We observed that 10 is the most efficient catalyst of the production of reactive oxygen species (ROS) and the most active anticancer agent in comparison to control monomers and their mixtures.
CRIS-Team Scopus Importer:2020-09-14

Detection of volatile metabolites of garlic in human breast milk - Scheffler, Laura; Sauermann, Yvonne; Zeh, Gina; Hauf, Katharina; Heinlein, Anja; Sharapa, Constanze; Büttner, Andrea (Metabolites, 2016)
The odor of human breast milk after ingestion of raw garlic at food-relevant concentrations by breastfeeding mothers was investigated for the first time chemo-analytically using gas chromatography−mass spectrometry/olfactometry (GC-MS/O), as well as sensorially using a trained human sensory panel. Sensory evaluation revealed a clear garlic/cabbage-like odor that appeared in breast milk about 2.5 h after consumption of garlic. GC-MS/O analyses confirmed the occurrence of garlic-derived metabolites in breast milk, namely allyl methyl sulfide (AMS), allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO2). Of these, only AMS had a garlic-like odor whereas the other two metabolites were odorless. This demonstrates that the odor change in human milk is not related to a direct transfer of garlic odorants, as is currently believed, but rather derives from a single metabolite. The formation of these metabolites is not fully understood, but AMSO and AMSO2 are most likely formed by the oxidation of AMS in the human body. The excretion rates of these metabolites into breast milk were strongly time-dependent with large inter-individual difference
Keywords: garlic; human milk; gas-chromatography mass-spectrometry; allyl methyl ulfide; allyl methyl sulfoxide; allyl methyl sulfone

Structure-Odor Relationships of (Z)-3-Alken-1-ols, (Z)-3-Alkenals, and (Z)-3-Alkenoic Acids - Lorber, Katja; Zeh, Gina; Regler, Johanna; Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2018)
Keywords: odor activity; odor intensity; chemo-communicative; gas chromatography-olfactometry; retention index; odor threshold in air; odorant